Питання літературознавства, 2021, № 103: Прийняти Іншого у своїй мові. Переклад як диспозитив медіації - Dzyk, Roman; Chervinska, Olha; Dranenko, Galyna (Yuriy Fedkovych Chernivtsi National University, 2021)
This monographic issue contains general theoretical, historical and literary materials that focus attention on the problems of the Inernational Colloquium “Accueillir l’Autre dans sa langue. La traduction comme dispositif de médiation” [“Welcoming the Other in One’s Language. Translation as a Mediation Dispositive”] (Chernivtsi, May 7–8, 2021). The articles are divided into four sections: “Linguistic Hospitality in Translation”, “Enrichment of the Target Language and Culture”, “Update of Theoretical Paradigms”, “Translation and Transcultural Mediation”.
Pitannâ lìteraturoznavstva, 2021, № 103: Accueillir l’Autre dans sa langue. La traduction comme dispositif de médiation
Keywords: Pitannâ lìteraturoznavstva; l’Autre; traduction